Direct PCR-RFLP based detection and differentiation of Anaplasma species in naturally infected goats of eastern Haryana, India - MAHARANA, BISWA RANJAN; GANGULY, ANITA; BISLA, RANBIR SINGH; ARORA, DEVAN; KUMAR, ANKIT; POTLIYA, SANDEEP; MISHRA, CHINMOY; GANGULY, INDRAJIT (The Indian Journal of Animal Sciences, 2019)
The present investigation was designed to develop a novel, rapid and cost effective direct PCR-RFLP assay, as a specific diagnostic tool for detection and differentiation of two Anaplasma species (A. ovis and A. marginale). Blood samples were collected randomly from 83 goats. A direct blood polymerase chain reaction (DT-PCR) for amplifying a fragment of the major surface protein 5 (msp5) gene of A. ovis/A. marginale from whole blood was developed and standardized. Blood smear examination revealed 24 samples (28.91%) positive for Anaplasma inclusion bodies. While, 39 (47%) samples were positive by DT-PCR. The results revealed that DT- PCR was 100% sensitive and 74.57% specific compared to microscopy based detection (k =0.62). Additionally DT-PCR showed 94.44% sensitivity and 100% specificity compared to conventional PCR results with suspected blood samples (k=0.94). All DT-PCR positive samples were confirmed to be A. ovis by restriction fragments length polymorphism (RFLP) analysis. The phylogenetic tree and sequence analysis revealed msp5 gene of Anaplasma species Indian isolate had maximum distance from A. phagocytophilum followed by A. centrale and A. marginale and 100% sequence identity with A. ovis isolates of Chinese origin which further confirmed the sequence identified in native goats to be of A. ovis. The simplified DT-PCR assay as a viable alternative to conventional PCR could be helpful for fast and accurate diagnosis of Anaplasma species and suitable for screening a large number of samples. Furthermore, results revealed that DT-PCR-RFLP of the msp5 gene might be a useful method for simultaneous detection and differentiation of A. ovis and A. marginale in goats.